Die klimatische Waldgrenze-Line oder Übergangsraum (Ökoton)? Ein Diskussionsbeitrag unter besonderer Berücksichtigung der Waldgrenzen in den mittleren und hohen Breiten der Nordhalbkugel - Holtmeier, Friedrich-Karl (ERDKUNDE, 1985)
In our days the opinion is widespread that under natural conditions the upper climatic forest limits would be rather sharp than a transitional belt. The existence of transitional belts is explained by unfavourable edaphic conditions and/or human influence. This concept has already been taken over in textbooks on plant geography. From his own experience in different timberline areas the present author does not agree with this opinion since the mountain and polar timberlines are so heterogeneous that they should not be generalized to such an extent. In fact, in various high mountains which have not or only randomly been influenced by Man the closed forest ends abruptly at its upper climatic limit. However, in some other high mountain areas as well as in the Subarctic the climatic timberline forms a more or less wide ecotone, extending from the closed forest to isolated crippled trees within the alpine belt or tundra. The existence of these ecotones cannot be primarily and everywhere attributed to human interferences and/or unfavourable edaphic conditions, but must be explained as the result of the complex influence of the actual and previous climate, fire, biotic factors and site history on tree growth. Furthermore, the different ecological requirements of the timberline species and their response to the environmental situation must also be considered. In many cases the existence of a timberline ecotone is the result of the oscillations of climate. Here the inertia of trees plays an important role. Many of them originated from seeds far beyond the closed forest during relatively warm periods and survived for hundreds of years although the climate became cooler. This is especially true for species which are able to regenerate and propagate vegetatively under conditions which would prevent sexual reproduction completely. On the other hand this does not mean that the whole ecotone was covered by forest in the past or could become completely forested in the future. The author gives some evidence that at many places the actual microclimatic conditions will prevent the progression of closed forest up to the actual treeline. In the end it depends on the local ecological situation and on site history whether the climatic forest limit is as sharp as a line or a more or less wide ecotone. As far as the Alps and some other high mountains are concerned, which have been similarly influenced by Man for thousands of years, there is no doubt that under natural conditions the closed forest would reach much higher and at places would also form an abrupt timberline, but there is no reason to assume that this would be the case everywhere.